1994
DOI: 10.2307/1131399
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Transitions in Early Adolescence on the Self-System and Perceived Social Context of Poor Urban Youth

Abstract: This study examined the effects of the normative school transition (n = 580) during early adolescence on the self-system and perceived school and peer social contexts of poor, black (n = 161), white (n = 146), and Latino (n = 273) youth in the public school systems of 3 eastern urban cities. The results revealed negative effects of the school transition on the affective and behavioral domains of the self-system. These declines in self-esteem, class preparation, and grade-point average (GPA) were common across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
167
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(187 citation statements)
references
References 24 publications
12
167
3
2
Order By: Relevance
“…Although this sample included Portuguese children who transitioned to secondary education 2 years earlier than students in the United Kingdom or the U.S. typically do, these findings are consistent with studies examining children who transition to secondary education at a later age (Wigfield et al, 1991). In addition, Seidman et al (1994) found that students’ academic self-perceptions declined even after adjusting for student age, grade level, and ability level. Together, these findings provide evidence that the transition process itself (i.e., the environment) as well as individual factors (e.g., developmental changes), likely play a role in changing children’s academic self-concept.…”
Section: The Effects Of the Transition To Secondary Education On Acadmentioning
confidence: 97%
See 2 more Smart Citations
“…Although this sample included Portuguese children who transitioned to secondary education 2 years earlier than students in the United Kingdom or the U.S. typically do, these findings are consistent with studies examining children who transition to secondary education at a later age (Wigfield et al, 1991). In addition, Seidman et al (1994) found that students’ academic self-perceptions declined even after adjusting for student age, grade level, and ability level. Together, these findings provide evidence that the transition process itself (i.e., the environment) as well as individual factors (e.g., developmental changes), likely play a role in changing children’s academic self-concept.…”
Section: The Effects Of the Transition To Secondary Education On Acadmentioning
confidence: 97%
“…A number of United States studies indicate that the transition from primary to secondary education has a negative impact on student grade point averages (GPA) and academic achievement (Felner et al, 1981; Simmons et al, 1991; Seidman et al, 1994; Alspaugh and Harting, 1995; Gutman and Midgley, 2000; Dotterer et al, 2009). Illustratively, United States students who moved from a primary to a secondary school experienced a decline in grades following the transition, unlike students who were in the same grade but had not transitioned to secondary education (Felner et al, 1981).…”
Section: The Effects Of the Transition To Secondary Education On Acadmentioning
confidence: 99%
See 1 more Smart Citation
“…Transitions to new schools are considered a stressful event (Barber & Olsen, 2004), and this transition may be related to changes in health and well-being among adolescents (Seidman & Allen, 1994; Symonds, Dietrich, Chow, & Salmela-Aro, 2016). Changes in the adolescents’ environment include such experiences as lessened contact with close friends (Darmody, 2008), changes in the structure of schooldays, downsized contact with teachers (Darmody, 2008; Pereira & Pooley, 2007), reduced support structures (Smyth, McCoy, & Darmody, 2004) and increased academic demands (Myklebust, 2002; Pereira & Pooley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These dispositions, in turn, have a strong impact on students' successful outcomes in education and beyond. Most of the existing studies of school transitions focus specifically on the transition from primary to lowersecondary level (see Seidman et al, 1994;Woods & Fraser, 1995;Youngman, 1996;Gutman & Midgley, 2000;Anderson et al, 2000;Kvalsund, 2000;Lucey & Reay, 2002), considering major structural and environmental changes involved. While this institutional transition point is widely researched, the transition from lower-secondary to upper-secondary schooling has received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%